Gdańsk Żuraw w czasie odbud[owy] - Lelewicz, Kazimierz (1896-1986). (Gdańsk - Wrzeszcz, 1958)
Przedstawia Żuraw podczas odbudowy.
Tyt. i data ołówkiem na rewersie.
Keywords: Fotografie -- Polska -- Gdańsk; Żuraw Wielki (Gdańsk, Polska ; brama) -- fotografie; Gdańsk (Polska) -- 1945-1970 -- fotografie